Asymptomatic Dengue Hepatitis: An Observational Study - Ahuja V; Ashish Bhagat; Sachdeva GS; Verma L (GMC Patiala Journal of Research and Medical Education, 2018)
Introduction: Dengue fever is an arthropod-borne acute febrile illness caused by dengue virus. During current epidemic of Dengue in our region high number of dengue patients were found to have deranged liver biochemistry. In this study we analysed 60 such patients for liver involvement.